Floristic composition of gold and uranium tailings dams, and adjacent polluted areas, on South Africa’s deep-level mines - I. M. Weiersbye (Bothalia: African Biodiversity & Conservation, 2006)
Gold and uranium tailings (‘slimes’) dams and the adjacent polluted soils in the deep-level mining regions of South Africa (Carletonville, Klerksdorp and Welkom) were surveyed for the frequency of occurrence of naturally colonizing, actively introduced and persisting plant species. Fifty-six tailings dams with a combined area of 5864 ha. and a similar area o f tail- ings-polluted soils, were surveyed between July 1996 and March 1997. During the survey, 376 plant species and subspecies were recorded from the dams and adjacent polluted soils, with an additional  8 6  records obtained between 1998 and 2003 (i.e. a total of 462 taxa: species and infraspecific species). Overall, the most commonly represented families were the Poaceae (107 species and subspecies), Asteraceae (81). Fabaceae (55) and Anacardiaceae (16). with other families represented by just one to 14 species. Only 60 species were common to all three regions, and of these 24 had been introduced during rehabilitation attempts. Most of the species found on tailings were persisters or natural colonizers (53-88%, depending on substrate), with the vast majority being indigenous and perennial taxa (76% and 85% respectively), with semi-woody to woody growth forms (6 6% being resprouters, forbs, shrubs and trees). Less than 4% of the naturally-colonizing taxa found during the survey had also been introduced by vegetation practitioners. The majority of introduced plants were alien herbaceous taxa. The number and frequency of annuals was only high on recently vegetated sites, whereas annuals were rarely present on old-vegetated and never-vegetated dams. This list includes a wide range of indigenous plant species that may be suitable for phytoremediation of tailings dams and polluted soils due to their apparent tolerance of acid mine drainage and salinity.